Coxeter group - Timothy, Kevin (2018)
This thesis is a summary of some chapters of James E. Humphreys's,``Reflection Groups and Coxeter Groups" in hope to help readers who are using the book to study Coxeter group. The thesis summarized chapters one, two, four and five of the book. This thesis will be focused much on the first chapter of the book, giving more examples and elaboration. Chapter one of the thesis talks about group generated by reflection, the properties we can get and the connection to Coxeter group. Chapter two states the possible classification of the Coxeter graph. Chapter three explains affine reflection groups and the Coxeter group from it. Chapter four finally talks about the Coxeter groups in abstract manner. Chapter five then concludes and give further studies related to Coxeter group.